OP0063 QUANTITATIVE COMPUTED TOMOGRAPHY PREDICTS 10-YEAR MORTALITY IN INTERSTITIAL LUNG DISEASE RELATED TO SYSTEMIC SCLEROSIS. (2nd June 2020) - Ariani, A.; Bravi, E.; De Santis, M.; Hax, V.; Parisi, S.; Lumetti, F.; Girelli, F.; Saracco, M.; De Gennaro, F.; Giollo, A.; Abdel Jaber, M.; Bozzao, F.; et al.
Abstract : Background: Interstitial lung disease (ILD) is the main cause of death in Systemic Sclerosis (SSc). Chest CT is the gold standard in detecting ILD although it is not easy to understand its prognostic value. ILD qualitative assessment is almost worthless. Goh et al. semi quantitative score of ILD extent is related to mortality risk but it is burdened by relevant inter/intra-readers variability. An operator independent algorithm based on voxel-wise analysis proved to identify SSc patients with an increased risk of mortality according to prediction models. Objectives: To verify if quantitative analysis of chest CT (QCT) predict 10 years-mortality in SSc patients. Methods: SSc patients with availability of a chest CT were enrolled in 13 different centers. The CT voxel-wise analysis with a free software (www.horosproject.com ) provided QCT indexes: kurtosis, skewness, mean lung attenuation and standard deviation. Patients characteristics, autoimmune profile and pulmonary function test were collected. The follow-up interval lasted from the date of chest CT to the one of the last visit or death. Each QCT index cutoff, established in a previous study (1), clustered patients in two groups. Kaplan-Meier analysis estimated and compared survival in the above mentioned groups. p < 0.05 was considered statistically significant. Results: Five hundred sixty three SSc patients were enrolled (35938 patient-months); 52.4% had ILD detectable at CT scan. For each QCT index cutoff the cohort was split in two subgroups without differences in terms of sex, age, disease duration, autoimmune profile. All QCT indexes' cutoff selected subgroups with statistically different survival rate (e.g in Figure 1 ). Conclusion: QCT can arise as the new gold standard in identifying SSc patients with poor prognosis. The real possibility to stratify SSc subjects according mortality risk will have a pivotal role in ILD treatment decisional process with the incoming anti-fibrotic drugs. References: [1]Ariani A et al. Rheumatology 2017 Disclosure of Interests: Alarico Ariani: None declared, Elena Bravi: None declared, Maria De Santis: None declared, Vanessa Hax: None declared, Simone Parisi: None declared, Federica Lumetti: None declared, Francesco Girelli: None declared, Marta Saracco: None declared, Fabio De Gennaro: None declared, Alessandro Giollo: None declared, Masen Abdel Jaber: None declared, Francesco Bozzao: None declared, Mario Silva: None declared, Maria Chiara Ditto: None declared, Claudia Lomater: None declared, Flavio Mozzani: None declared, Daniele Santilli: None declared, eleonora Di Donato: None declared, Andrea Becciolini Speakers bureau: Sanofi-Genzyme, UCB and AbbVie, Francesco Pucciarini: None declared, Lorenzo Canziani: None declared, Flavio Cesare Bodini: None declared, eugenio arrigoni: None declared, M Bredemeier: None declared, Rafael Mendonça da Silva Chakr: None declared, Amelia Spinella: None declared, Luca Idolazzi: None declared, Roberto Bortolotti: None declared, Paola Tomietto: None declared, Elisa Baratella: None declared, Saverio Tollot: None declared, Dilia Giuggioli: None declared, Fabio Fischetti: None declared, Enrico Fusaro: None declared, Nicola Sverzellati: None declared, Carlo Alberto Scirè: None declared